2014
DOI: 10.3109/0284186x.2014.948060
|View full text |Cite
|
Sign up to set email alerts
|

High-dose proton beam therapy for stage I non-small cell lung cancer: Clinical outcomes and prognostic factors

Abstract: respectively. There were no significant differences in outcomes between the two protocols. Late grade 2 and 3 pulmonary toxicities were observed in nine patients (13.4%) and one patient (1.5%), respectively; no grade 4 or 5 toxicities were observed. Sex, age, performance status, T-stage, operability, and tumor pathology were not associated with OS and PFS.Only maximum standardized uptake value (SUV max ;  5 vs.  5) was identified as a significant prognostic factor for OS and PFS. conclusion. Both high-dose P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 26 publications
3
31
1
Order By: Relevance
“…[11][12][13][14][15] Hypofractionated, high-dose PBT has been used to treat inoperable patients or patients who refuse to undergo surgery in Japan, and previous single-institute studies have demonstrated promising results of PBT for stage I NSCLC. [18][19][20] The present study is the first multiinstitutional study to evaluate the feasibility and efficacy of PBT for stage I NSCLC in a large number of patients. These results may therefore represent the outcomes of PBT Abbreviations: LPF Z local progression-free rate; OS Z overall survival; PFS Z progression-free survival; PS Z performance status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15] Hypofractionated, high-dose PBT has been used to treat inoperable patients or patients who refuse to undergo surgery in Japan, and previous single-institute studies have demonstrated promising results of PBT for stage I NSCLC. [18][19][20] The present study is the first multiinstitutional study to evaluate the feasibility and efficacy of PBT for stage I NSCLC in a large number of patients. These results may therefore represent the outcomes of PBT Abbreviations: LPF Z local progression-free rate; OS Z overall survival; PFS Z progression-free survival; PS Z performance status.…”
Section: Discussionmentioning
confidence: 99%
“…In recent institutional retrospective studies of patients with stage I NSCLC treated with PBT, the 3-year OS and LC rates ranged from 75% to 81% and from 81% to 96%, respectively; grade 3 RP was observed in 1.3% to 1.7% of patients. [18][19][20] Whether PBT improves survival and LC while also decreasing the incidence of radiation-induced toxicities compared with SBRT in patients with stage I NSCLC remains unclear. Only one randomized phase 2 study has compared SBRT and PBT for early-stage NSCLC; this study ended prematurely because of poor accrual.…”
Section: Introductionmentioning
confidence: 99%
“…The OS, PFS and LC for the entire cohort were 81.3%, 73.4%, and 96%, respectively, at 3 years, with no grade 4 or 5 toxicities reported, and grade 3 toxicities limited to two patients; one with dermatitis and the other with pneumonitis. 54 …”
Section: Proton Therapy In Early Stage Nsclcmentioning
confidence: 99%
“…In clinical studies, Japanese centers reported promising local control and feasibility for central tumors using a more fractionated schedule PBT. 26 , 27 Makita et al 27 reported that they treated 24 central tumors with 80 Gy (RBE) in 25 fractions, and no one experienced late grade 3 or severe toxicities. These promising results have some limitations in that these are retrospective studies with a small number of patients.…”
Section: Introductionmentioning
confidence: 99%